2020
DOI: 10.1042/bsr20194370
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the miR-19b-mediated SOCS6-JAK2/STAT3 pathway by lncRNA MEG3 is involved in high glucose-induced apoptosis in hRMECs

Abstract: Objective: Diabetic retinopathy (DR) is one of the most severe and common complications of diabetes mellitus. The present study aimed to investigate the molecular mechanism of MEG3, miR-19b and SOCS6 in human retinal microvascular endothelial cells (hRMECs) under high glucose conditions. Methods: HRMECs were cultured in 5 or 30 mM D-glucose medium. qRT-PCR and Western blotting were used to determine the mRNA expression and protein levels. MTT assay and flow cytometry analysis were performed to detect the viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Our results suggested that PVT1 had great potential as a diagnostic biomarker for patients with DR. The abnormal behavior of HRMECs has been confirmed to be closely associated with a variety of retinal vascular diseases and played an important role in DR [34]. Furthermore, the dysregulation of lncRNA can regulate the proliferation and migration of HRMECs in the high glucose environment, such as MALAT1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that PVT1 had great potential as a diagnostic biomarker for patients with DR. The abnormal behavior of HRMECs has been confirmed to be closely associated with a variety of retinal vascular diseases and played an important role in DR [34]. Furthermore, the dysregulation of lncRNA can regulate the proliferation and migration of HRMECs in the high glucose environment, such as MALAT1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no studies have investigated the role of JAK2/STAT3 signaling in CIN. It was reported that the phosphorylated activation of JAK2/STAT3 played a part in the induction of apoptosis, autophagy, inflammation, and oxidative stress and that the activation of the JAK2-STAT3 signaling pathway protected tissue against acute injury in some studies (35)(36)(37). In contrast, the renoprotective effect of curcumin in AKI caused by lipopolysaccharide (LPS) or severe acute pancreatitis may be associated with inflammation reduction mediated by suppression of JAK2/STAT3 signaling pathway (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, TPTEP1 can inhibit the phosphorylation and nuclear translocation of STAT3, thereby downregulating VEGFA mRNA and protein levels and hindering the formation of new blood vessels under HG conditions ( 68 ). MEG3 negatively regulates miR-19b to inhibit HG-induced inflammatory factors generated from HMRECs, caspase-3/7 and cell apoptosis ( 69 ). Therefore, reversing the expression level of lncRNAs under certain conditions may play a role in promoting the alleviation of DR.…”
Section: Three Types Of Rna Influence the Development Of Dr Through Microvascular Endothelial Cellsmentioning
confidence: 99%